2014
DOI: 10.1186/1476-4598-13-181
|View full text |Cite
|
Sign up to set email alerts
|

ISL-1 is overexpressed in non-Hodgkin lymphoma and promotes lymphoma cell proliferation by forming a p-STAT3/p-c-Jun/ISL-1 complex

Abstract: BackgroundInsulin enhancer binding protein-1 (ISL-1), a LIM-homeodomain transcription factor, is essential for the heart, motor neuron and pancreas development. Recently, ISL-1 has been found in some types of human cancers. However, how ISL-1 exerts the role in tumor development is not clear.Methods and resultsThe expression of ISL-1 was assessed in 211 human lymphoma samples and 23 normal lymph node samples. Immunohistochemistry results demonstrated a markedly higher expression of ISL-1 in 75% of non-Hodgkin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Previously, we proved that ISL1 promoted the proliferation of adult pancreatic islet cells and lymphoma cells [10, 11]. To determine the role of ISL1 in GC, we established stable ISL1-overexpressing and knockdown MKN28 and MGC803 (thereafter labeled as MGC) cell lines using pcDNA3.1-ISL1 and pLL3.7-ISL1-siRNA plasmids, respectively (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we proved that ISL1 promoted the proliferation of adult pancreatic islet cells and lymphoma cells [10, 11]. To determine the role of ISL1 in GC, we established stable ISL1-overexpressing and knockdown MKN28 and MGC803 (thereafter labeled as MGC) cell lines using pcDNA3.1-ISL1 and pLL3.7-ISL1-siRNA plasmids, respectively (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Hansel et al [26] used global gene expression analysis and reported that ISL-1 was overexpressed in human biliary cancer. ISL-1 has also been found to participate in metastasis in pancreatic neuroendocrine neoplasms, pancreatic endocrine tumors, non-muscle-invasive bladder cancer, and non-Hodgkin lymphoma [19][20][21][22]. In addition, the level of ISL-1 protein expression is closely associated with the development of cancer, cancer cell growth, and metastasis, as well as the prognosis of patients with pancreatic endocrine tumors [21].…”
Section: Discussionmentioning
confidence: 96%
“…The plasmid pcDNA3-ISL1 and control vector pcDNA3 were separately transfected into NIH3T3 cells to establish stable ISL-1-overexpressing cells (pcDNA3-ISL-1) and control cells (pcDNA3), as previously described [22]. Five-week-old female nude mice were subcutaneously injected on the right side of the dorsum (pcDNA3-ISL-1) and left armpit (pcDNA3) with 1 × 10 7 cells suspended in 200 μL phosphate-buffered saline (PBS).…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of signal transducer and activator transcription 3 (STAT3) is one of the reasons for refractory cases of DLBCL [5-7]. STAT3 signaling regulates the expression of genes that control tumor cell growth, drug resistance, and clonogenicity, and is associated with cancer stem cell characteristics [8, 9]. STAT3 is usually activated in the non-GCB group of DLBCL, while the expression of phosphorylated (p)-STAT3 goes undetected in several GCB DLBCL cell lines [10].…”
Section: Introductionmentioning
confidence: 99%